Uso de las redes sociales por parte de los estudiantes de la carrera de Pedagogía de las Ciencias Experimentales: Informática durante el periodo mayo – septiembre 2021. - Prócel Caiza, Roberto Carlos (2022)
Nowadays, social networks are an important resource, this is how in the educational field they have become a priority for students, because they are easily accessible through cell phones, computers and tablets, and sometimes they are given a misuse. Due to the aforementioned, the present research work aims to know the characteristics of access, time of use and utility social networks by the students of the Computer Pedagogy Career of the National University of Chimborazo during the period May – September 2021. The research methodology had a quantitative approach with a descriptive scope and a non- experimental cross-sectional design because the data collected in a single moment, in addition, the entire population worked with, which were 130 students. The information collected through a questionnaire adapted from one published. Among the main results obtained, it can be mentioned that social networks are used mostly for communication between students and not for the academic field.